2020
DOI: 10.1111/jsap.13110
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation of elbow congruity in dogs: radial incisure versus apical medial coronoid process fragmentation

Abstract: Objectives To compare elbow congruity in two cohorts of Labrador retrievers affected with either radial incisure or apex fragmentation of the medial coronoid process. Materials and Methods Dogs were included if they had elbow lameness and a CT diagnosis of a fissure or fragmentation of the medial coronoid process occurring either along the radial incisure or at the coronoid apex. Radioulnar joint space was measured incrementally from the lateral to the medial coronoid process on transverse slice images. Axial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 18 publications
(38 reference statements)
2
18
1
Order By: Relevance
“…Radioulnar congruency has previously been investigated in Labradors as a potential cause of radial incisure-located versus apical medial coronoid fragmentation; however, no clear role of change in congruency explained the difference in pathology. 19 The influence of congruency in this location remains under-evaluated and poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Radioulnar congruency has previously been investigated in Labradors as a potential cause of radial incisure-located versus apical medial coronoid fragmentation; however, no clear role of change in congruency explained the difference in pathology. 19 The influence of congruency in this location remains under-evaluated and poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Primary changes in the kinematics of the radius, ulna and humerus are assumed to play an role in the pathogenesis of MCD. Altered kinematics in the proximal radio-ulnar joint, were suggested by different researchers to be one potential factor influencing the development of MCD [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90]. One proposed mechanism was an increased axial translation of the radius relative to the ulna leading to an dynamic radio-ulnar incongruence.…”
Section: The Dysplastic Elbow Jointmentioning
confidence: 99%
“…Especially in dogs without a measurable static incongruence, which account for 40% of all patients with MCD [76], the insufficient adaption to intra articular joint loads can lead to mechanical overload at one distinct joint compartment. Increased radio-ulnar rotation was proposed as another potential cause of mechanical overload along the radial incisure of the medial coronoid process and subsequent cartilage and bone damage [82,[87][88][89][90]. The only study comparing in vivo radio-ulnar rotational movement in healthy joints to joints with MCD showed no significant difference in the total amount of radial rotation and in the motion pattern of the radius [74].…”
Section: The Dysplastic Elbow Jointmentioning
confidence: 99%
“…Multi‐directional dynamic incongruities have been reported to be one of the main contributors to fissuring and/or fragmentation of the medial coronoid process (MCP) with multiple variations in the location of ulnar osteochondral lesions 1 . Pathological changes in the MCP are variable because of the complex biomechanics of the elbow joint and often not related to the severity of clinical presentation 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…1 Pathological changes in the MCP are variable because of the complex biomechanics of the elbow joint and often not related to the severity of clinical presentation. [4][5][6] CT has been postulated to be the most sensitive and specific non-invasive diagnostic tool for classifying and evaluating all components of MCD lesions and has a sensitivity of 100% and a specificity of 93%. 7 It has also been suggested that lesions may be restricted to the apex of the MCP or radial incisure or may involve the medial and/or lateral aspect of the MCP depending on the radioulnar articulation of the individual elbow joint.…”
Section: Introductionmentioning
confidence: 99%